2017
DOI: 10.18632/oncotarget.21404
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic hexapeptide (PGPIPN) prevents and cures alcoholic fatty liver disease by affecting the expressions of genes related with lipid metabolism and oxidative stress

Abstract: PGPIPN is a therapeutic hexapeptide derived from bovine β-casein. Here we investigated the role and mechanism of this peptide on alcoholic fatty liver disease (AFLD). We took human hepatic cell line LO2 and hepatocellular carcinoma cell line HepG2 to establish the models of steatosis hepatocyte induced by alcohol, taken PGPIPN as pharmacological intervention. And we also established the model of AFLD mice, taken PGPIPN as therapeutic drug and glutathione (GSH) as positive control. We assayed the biochemical ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…On the other hand, mounting studies have convinced that inflammation plays an essential role in the initiation and development of AFLD [ 16 , 17 ]. Furthermore, considerable research has reported that long-term alcohol consumption could influence multiple signaling pathways for lipid metabolism, which increase lipogenesis, inhibit β -oxidation of fatty acids, and cause hepatocytes steatosis [ 18 , 19 ]. Although immediate alcohol abstinence is the most effective therapeutic treatment for AFLD, it is very difficult to carry out for persons with alcohol dependence [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, mounting studies have convinced that inflammation plays an essential role in the initiation and development of AFLD [ 16 , 17 ]. Furthermore, considerable research has reported that long-term alcohol consumption could influence multiple signaling pathways for lipid metabolism, which increase lipogenesis, inhibit β -oxidation of fatty acids, and cause hepatocytes steatosis [ 18 , 19 ]. Although immediate alcohol abstinence is the most effective therapeutic treatment for AFLD, it is very difficult to carry out for persons with alcohol dependence [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Pro-Gly-Pro-Ile-Pro-Asn (PGPIPN) is a hexapeptide derived from the 63-68 amino acid residue of bovine β-casein [21]. We found in previous experiments that PGPIPN could effectively reduce inflammation and promote the immune of body, thereby reducing alcoholic liver injury [22,23]. It also can inhibit the proliferation, invasion and metastasis of ovarian cancer cells and induce the cells apoptosis [18,24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Bioactive peptides derived from proteins are beneficial to human health, and were reported to possess numerous biological activities, such as anti-oxidation, anti-hypertension, anti-diabetes and immune regulation, and also play important roles in regulating immune responses and certain physiological functions in vivo ( 10 - 12 ). Previous studies revealed that bioactive peptides play an important role in early ALI and chronic alcoholic injury in mice ( 13 , 14 ), and can promote alcohol clearance and bile acid metabolism, as well as reduce serum the levels or activities of total cholesterol (TC), triglyceride (TG), alanine aminotransferase (ALT) and aspartate aminotransferase (AST) ( 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, PGPIPN inhibited cell proliferation and induced cell apoptosis in the human ovarian cancer cell line SKOV 3 in vitro and reduced tumor growth rates in mice ( 21 ). Recent studies showed that PGPIPN can alleviate alcoholic fatty liver disease ( 13 ). Therefore, the aim of the present study was to investigate whether PGPIPN can alleviate AALI in mice.…”
Section: Introductionmentioning
confidence: 99%